Physical fitness standards: An assessment of potential disparate impact for female state police applicants - Williams, Frederick A (International journal of police science & management, 2022)
To improve diversity in hiring, this quantitative study examines the applicant physical fitness testing standards of the Kentucky State Police (KSP) to determine whether the test or specific events have a disparate impact for female state police applicants. A sample of 427 state police applicants was collected from applicant fitness testing conducted by the KSP between 2014 and 2019. Bivariate analysis was used to compare the output of males and females. Logistic regression was used to determine predictors for passing fitness testing. The results show a potential disparate impact based upon significant performance differences in three of the five fitness events: bench press, 300-meter run, and push-ups. Predictors for passing applicant fitness testing were being male, having a lower body weight and having 2 years of military service. Sex was found to be a predictor for passing push-ups and 300-meter run. Recommendations suggest amending the fitness events, establishing equitable scoring criteria based upon sex without averaging, and reassessment and evaluation. Provisions for evaluation were provided.